2019
DOI: 10.1055/s-0039-1698718
|View full text |Cite
|
Sign up to set email alerts
|

Role of Anthropometric Nutritional Assessment in Severe Head Injury

Abstract: Aim Nutritional demand after traumatic brain injury is increased due to hypermetabolic response. The present study was undertaken to assess nutritional status with anthropometric indices, factors associated, and their prognostic role following severe head injury (SHI). Method A total of 114 patients in age group 20 to 60 years, admitted within 24 hours of SHI, with Glasgow Coma Scale of 4 to 8, and with no serious systemic disorder were enrolled for the study. Of these, 67 were prospectively assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…In the same way Hartgrink et al (2016) had proved that supplemental feeding improves the nutritional status, but there wasn't a relation with DUs development and severity. Meanwhile, a study carried out by Dhandapani et al (2018) found that the delayed attainment of eternal feeding influence the occurrence of DUs. This may berelated to the delayed calories replacement along with hyper metabolism result in muscle atrophy, diminished subcutaneous fat, and finally leading to DUsdevelopment.…”
Section: Concerning Methods Of Feedingmentioning
confidence: 99%
“…In the same way Hartgrink et al (2016) had proved that supplemental feeding improves the nutritional status, but there wasn't a relation with DUs development and severity. Meanwhile, a study carried out by Dhandapani et al (2018) found that the delayed attainment of eternal feeding influence the occurrence of DUs. This may berelated to the delayed calories replacement along with hyper metabolism result in muscle atrophy, diminished subcutaneous fat, and finally leading to DUsdevelopment.…”
Section: Concerning Methods Of Feedingmentioning
confidence: 99%